Effects of high-intensity interval training versus moderate-intensity continuous training on cardiorespiratory and exercise capacity in patients with coronary artery disease: A systematic review and meta-analysis - Chao Gao; Yuchuan Yue; Dongmei Wu; Junming Zhang; Shuyao Zhu (PLoS ONE, 2025)
Background With the increasing utilization of cardiac rehabilitation in clinical treatment and prognosis for patients with cardiovascular diseases, exercise training has become a crucial component. High-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) are commonly employed in rehabilitating patients with cardiovascular diseases. However, further investigation is required to determine whether HIIT and MICT can effectively enhance the prognosis of patients with coronary artery disease. Therefore, this study aims to assess the effectiveness of HIIT and MICT interventions, optimal intervention duration for different intensity levels of training, as well as effective training modalities that improve cardiorespiratory function and exercise capacity among patients. Methods We conducted a comprehensive search of the Cochrane Library, PubMed, EMbase, Web of Science, and CINAHL databases for randomized controlled trials (RCTs) pertaining to high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) interventions in patients with coronary artery disease from inception until publication on September 26, 2024. Two independent researchers assessed articles that met the inclusion criteria and analyzed the results using Sata 17.0 software. Forest plots were employed to evaluate the impact of HIIT and MICT on outcome indicators. Sensitivity analysis and funnel plot assessment were performed to examine publication bias. Subgroup analysis was conducted to determine optimal intervention duration and training methods. Results A total of 22 studies with 1364 patients were included in the study, including the HIIT group (n = 685) and the MICT group (n = 679). The results showed that compared to MICT, HIIT significantly increased PeakVO2(Peak oxygen uptake)[WMD = 1.42mL /kg/min 95%CI (0.87, 1.98), P = 0.870, I2 = 0%], 6MWT(6-minute walk test)[WMD = 18.60m 95%CI (2.29, 34.92), P = 0.789, I2 = 0%], PHR(Peak heart rate)[WMD = 4.21bpm 95%CI (1.07, 7.36), P = 0.865, I2 = 0%], DBP(diastolic blood pressure)[WMD = 3.43mmHg 95%CI (1.09, 5.76), P = 0.004, I2 = 60.2%]. However, in LVEF(left- ventricular ejection fraction)[WMD = 0.32mL 95%CI (-1.83, 2.46), P = 0.699, I2 = 0%], LVEDV(left ventricular end-diastolic volume)[WMD = 0.91 ml 95%CI (-1.83, 2.46), P = 0.995, I2 = 0%] and SBP(systolic blood pressure)[WMD = 1.85mmHg 95%CI (-0.23, 3.93),P = 0.266, I2 = 18.2%], there was no significant difference between HIIT and MICT. Conclusion Based on the findings of this systematic review, HIIT demonstrates superior efficacy compared to MICT in enhancing PeakVO2, PHR, 6MWT and DBP. However, no significant differences were observed in LVEF, LVEDV, and SBP. In summary, HIIT exhibits potential for improving cardiopulmonary function and exercise capacity among patients with coronary artery disease.